Screening canine sources for novel antimicrobials reveals the circular broad-spectrum bacteriocin, caledonicin, produced by Staphylococcus caledonicus - O’Connor, Michelle; O’Connor, Paula M.; Hourigan, David; Murray, Ellen; de Farias, Felipe Miceli; Field, Des; Hill, Colin; Ross, R. Paul (Frontiers in Microbiology, 2024)
Antimicrobial-resistant pathogens present an ongoing threat to human and animal health, with deaths linked to antimicrobial resistance (AMR) predicted to increase yearly. While the misuse and overuse of antibiotics in humans undoubtedly contribute to this escalation, antibiotic use in the veterinary field, including companion animals, also plays a contributing role. Pet owners' desire to improve the quality of life of their pets is likely to support antibiotic use within this field. Consequently, there is a need for antibiotic alternatives to treat bacterial infections. This study set out to screen for antimicrobial peptides known as bacteriocins from bacterial isolates of aerobic/microaerophilic environments of canine sources and determine their potential as antibiotic alternatives against clinically relevant pathogens. Following a laboratory-based protocol, 22 bacterial isolates were subjected to whole genome sequencing (WGS) and a total of 14 putative novel bacteriocins were identified from both class I and II bacteriocin classes.One particular bacteriocin, herein named caledonicin, was identified via in silico analysis from a Staphylococcus caledonicus strain, and partially purified for further in vitro evaluation. Caledonicin is a 64 amino acid (IAANLGVSSGTAYSMANALNNISNVATALTIIGTFTGVGTIGSGIAATILAILKKKGV AAAAAF) novel circular bacteriocin most closely related to enterocin_NKR-5-3B based on core peptide alignment (39.1%), with a molecular weight of 6077.1 Da. Caledonicin exhibits a broad spectrum of activity against a range of pathogenic bacteria, including methicillinresistant Staphylococcus aureus (MRSA), methicillin-resistant Staphylococcus pseudintermedius (MRSP), and Listeria monocytogenes; and the gut related bacterium associated with Crohn's disease, Mediterraneibacter gnavus ATCC 29149 (previously Ruminococcus gnavus ATCC 29149). This represents the first bacteriocin screening study involving bacteria from canine sources and confirms this is a rich environment for bacteriocinproducing strains. This study also identifies and characterises the first novel bacteriocin from the staphylococcal species, Staphylococcus caledonicus.